2018
DOI: 10.1194/jlr.m081307
|View full text |Cite
|
Sign up to set email alerts
|

An intrinsic lipid-binding interface controls sphingosine kinase 1 function

Abstract: Sphingosine kinase 1 (SK1) is required for production of sphingosine-1-phosphate (S1P) and thereby regulates many cellular processes-including cellular growth, immune cell trafficking, and inflammation. To produce S1P, SK1 must access sphingosine directly from membranes. However, the molecular mechanisms underlying SK1's direct membrane interactions remain unclear. We used hydrogen-deuterium exchange mass spectrometry to study interactions of SK1 with membrane vesicles. Using the CRISPR/Cas9 technique to gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 62 publications
2
35
0
Order By: Relevance
“…Upon closer examination of the currently published SK1 structures, Adams et al proposed a mechanism by which SK1 can form dimers and interact with membranes using a single contiguous interface [78]. Our lab has recently identified a new electrostatic site on SK1 and has shown that it forms a single interface, along with the hydrophobic patch, to effectively interact with membranes [80]. sdf This single contiguous interface is critical for the function of SK1 in cells [80].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Upon closer examination of the currently published SK1 structures, Adams et al proposed a mechanism by which SK1 can form dimers and interact with membranes using a single contiguous interface [78]. Our lab has recently identified a new electrostatic site on SK1 and has shown that it forms a single interface, along with the hydrophobic patch, to effectively interact with membranes [80]. sdf This single contiguous interface is critical for the function of SK1 in cells [80].…”
Section: Introductionmentioning
confidence: 99%
“…Our lab has recently identified a new electrostatic site on SK1 and has shown that it forms a single interface, along with the hydrophobic patch, to effectively interact with membranes [80]. sdf This single contiguous interface is critical for the function of SK1 in cells [80]. Together the work of Pulkoski-Gross et al [80], Shen et al [79], and Adams et al [78] provide insight into an intrinsic mechanism for SK1 interaction with membranes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The SK1 Leu 194 residue, which was shown to be an important part of membrane binding activity of SK1 in the study by Pulkoski-Gross et al (10) as well as a previous study (5), is part of an -helix with several exposed hydrophobic residues (Leu 187 , Met 189 , and Leu 198 ) (See Fig. 1).…”
Section: Experiments With Hydrogen-deuterium Exchange Mass Spectrometmentioning
confidence: 99%
“…In this issue of J. Lipid Res., Pulkoski-Gross et al examine the ability of SK1 to interact with anionic membranes based upon the SK1 structure (10). Despite the structure of SK1 being solved more than four years ago, there has been little mechanistic information on how SK1 accesses its substrate in the context of membranes.…”
Section: *Corresponding Author: Rstaheli@purdueedumentioning
confidence: 99%